2001
DOI: 10.1210/endo.142.9.8389
|View full text |Cite
|
Sign up to set email alerts
|

Functional Segregation of the Highly Conserved Basic Motifs within the Third Endoloop of the Human Secretin Receptor

Abstract: In this study, a mutagenesis-based strategy was employed to assess the roles of two highly conserved motifs (KLR and RLAR) within the third endoloop of the human secretin receptor. Block deletion of KLRT and mutation of Lys323 (K 323 I) significantly reduced cAMP accumulation, and these mutations did not affect ligand interaction and receptor number expressed on the cell surface. Thus, the KLRT region at the N terminus of the third endoloop, particularly Lys323, is important for G protein coupling. For the RLA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 58 publications
2
6
0
Order By: Relevance
“…This is consistent with many observations indicating that the IL3 of class I receptors interacts with G␣ and G␤ subunits of G proteins and is important for signal transduction (Ref. 29 (34), and PTH1 receptor (35) signaling. Moreover, splice variants of the specific PACAP receptor PAC1 have been described with insertion of 28 -56-amino acid cassettes within IL3 (36).…”
Section: Hvpac1 Receptor Cytoplasmic Domainssupporting
confidence: 93%
“…This is consistent with many observations indicating that the IL3 of class I receptors interacts with G␣ and G␤ subunits of G proteins and is important for signal transduction (Ref. 29 (34), and PTH1 receptor (35) signaling. Moreover, splice variants of the specific PACAP receptor PAC1 have been described with insertion of 28 -56-amino acid cassettes within IL3 (36).…”
Section: Hvpac1 Receptor Cytoplasmic Domainssupporting
confidence: 93%
“…This was achieved with the KLT R325A-K328A mutant that did not respond to VIP. These results, in line with previous studies performed on other members of the GPCR-B family that identified the proximal domain of IC 3 loop as essential for G s coupling and adenylate cyclase activation (Huang et al 1996, Takhar et al1996, Chan et al 2001, Couvineau et al 2003 A-K 328 A) was insensitive to GTP, indicating that the global measure of GTP effects reflects the coupling of both G s and G 16 to the receptor. The junctions of IC 3 loop are predicted to be -helical and it is assumed that the correct positioning of charged amino acids plays a crucial role in G protein interaction.…”
Section: Discussionsupporting
confidence: 89%
“…Sitedirected mutagenesis of residues in similar cytosolic face regions of these receptors has also produced loss-of-function phenotypes, but the details of the molecular basis for exposure of these regions for G protein association is currently unclear (Chan et al, 2001;Tams et al, 2001).…”
Section: Tm Receptors As Shapeshifting Proteinsmentioning
confidence: 99%